Antiviral effect of cationic compounds on bacteriophages - Chatain-Ly, Mai Huong; Moussaoui, Saliha; Rigobello, Veronique; Demarigny, Yann; Vera, Annabelle (Frontiers in Microbiology, 2013)
The antiviral activity of several cationic compounds - cetytrimethylammonium (CTAB), chitosan, nisin and lysozyme - was investigated on the bacteriophage c2 (DNA head and non-contractile tail) infecting Lactococcus strains and the bacteriophage MS2 (F-specific RNA) infecting E.coli. Firstly, these activities were evaluated in a phosphate buffer pH 7- 10 mM. The CTAB had a virucidal effect on the Lactococcus bacteriophages, but not on the MS2. After 1 min of contact with 0.125 mM CTAB, the c2 population was reduced from 6 log(pfu)/mL to 1,5 log(pfu)/mL and completely deactivated at 1 mM. On the contrary, chitosan inhibited the MS2 more than it did the bacteriophages c2. No antiviral effect was observed for the nisin or the lysozyme on bacteriophages after 1 min of treatment. A 1 and 2.5 log reduction was respectively observed for nisin and lysozyme when the treatment time increased (5 or 10 min). These results showed that the antiviral effect depended both on the virus and structure of the antimicrobial compounds. The antiviral activity of these compounds was also evaluated in different physico-chemical conditions and in complex matrices. The antiviral activity of CTAB was impaired in acid pH and with an increase of the ionic strength. These results might be explained by the electrostatic interactions between cationic compounds and negatively charged particles such as bacteriophages or other compounds in a matrix. Milk proved to be protective suggesting the components of food could interfere with antimicrobial compounds.